2007
DOI: 10.1007/bf03175359
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) degrading actinomycetes and purification of PHBV depolymerase from newly isolatedStreptoverticillium kashmirense AF1

Abstract: Streptoverticillium kashmirense AF1 with the ability to degrade a natural polymer, poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) was isolated from municipal sewage sludge by soil burial technique. The PHBV film was degraded by the action of extracellular enzymes secreted by the microorganisms. Degradation of PHBV was evident by the formation of clear zones of hydrolysis on the polymer containing mineral salt agar plates. The extent of PHBV degradation increased up to 30 days of incubation. Maximum produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…PHBV depolymerase of Bacillus sp. AF3 and Streptoverticillium kashmirense AF1 have also been purified on Sephadex G-75 [30]. Kim et al [31] have also purified PHB depolymerase of Emericellopsis minima W2 and Streptomyces sp.…”
Section: Production Of Phb Depolymerasementioning
confidence: 99%
“…PHBV depolymerase of Bacillus sp. AF3 and Streptoverticillium kashmirense AF1 have also been purified on Sephadex G-75 [30]. Kim et al [31] have also purified PHB depolymerase of Emericellopsis minima W2 and Streptomyces sp.…”
Section: Production Of Phb Depolymerasementioning
confidence: 99%
“…Thus, column chromatography using an octyl-sepharose CL - 4B column resulted in the most efficient purification. Purification of PHB depolymerase from various organisms has been carried out using Sephadex columns [3334]. Wang et al [29], DEAE-Sepharose column and using column chromatography [6–8].…”
Section: Resultsmentioning
confidence: 99%
“…Purification of PHB depolymerase from various organisms has been carried out using Sephadex columns, e.g., PHB depolymerase of Bacillus sp. (1.79 U/mg) (Shah et al 2007) (32) Streptoverticillium kashmirense AF1, and Streptomyces ascomycinicus (Garcia et al 2013) (33). Wang et al (2012) (28) reported the purification of an extracellular PHB depolymerase from Pseudomonas mendocina DSWY0601 using a DEAE-Sepharose column.…”
Section: Resultsmentioning
confidence: 99%